Superstructure formation in SrBa8[BN2]6 and EuBa8[BN2]6. Issue 30 (11th July 2016) - Seidel, Stefan; Dierkes, Tobias; Jüstel, Thomas; Benndorf, Christopher; Eckert, Hellmut; Pöttgen, Rainer
Abstract : X-ray pure samples of SrBa8 [BN2 ]6 and EuBa8 [BN2 ]6 were synthesized from appropriate amounts of binary nitrides (Sr3 N2, Ba3 N2 and BN in sealed niobium ampoules and EuN, Ba3 N2 and BN in BN crucibles, respectively) at temperatures up to 1370 K. Abstract : X-ray pure samples of SrBa8 [BN2 ]6 and EuBa8 [BN2 ]6 were synthesized from appropriate amounts of binary nitrides (Sr3 N2, Ba3 N2 and BN in sealed niobium ampoules and EuN, Ba3 N2 and BN in BN crucibles, respectively) at temperatures up to 1370 K. The structure of SrBa8 [BN2 ]6 was refined from single crystal X-ray diffractometer data: Fd 3̄ m, a = 1595.1(1) pm, w R ( F 2 ) = 0.0515, 387 F 2 values and 21 variables. EuBa8 [BN2 ]6 has a lattice parameter of 1595.00(9) pm. Both nitridoborates adopt a new 2 × 2 × 2 superstructure variant of the LiCa4 [BN2 ]3 type, realized through ordering of vacancies and Sr 2+ and Eu 2+ cations, respectively. The structures of SrBa8 [BN2 ]6 and LiCa4 [BN2 ]3 are related by a group–subgroup scheme. The Sr 2+ /vacancy ordering leads to an asymmetric coordination (1 × Sr 2+ and 8 × Ba 2+ in a distorted, mono-capped square prism) for the [BN2 ] 3− units with B–N distances of 132 and 136 pm. Vibrational spectra of SrBa8 [BN2 ]6 and EuBa8 [BN2 ]6 confirm the discrete linear [BN2 ] 3− units and 11 B solid state MAS NMR spectra are compatible with single crystallographic sites for the boron atoms. In EuBa8 [BN2 ]6 the spectra are profoundly influenced by interactions of the 11 B nuclei with the unpaired electrons of the paramagnetic Eu 2+ ions.